2022
DOI: 10.3389/frsc.2022.930061
|View full text |Cite
|
Sign up to set email alerts
|

Toward circular and socially just urban mining in global societies and cities: Present state and future perspectives

Abstract: This study evaluates the perspectives of urban mining in the framework of the circular economy (CE) and starts with a brief analysis of the size of global and urban metabolism and the role that plays materials and waste streams such as construction and demolition waste (C&DW) and waste from electronic and electrical equipment (WEEE). These can be considered as temporary stocks or deposits to be mined in the future, thus shedding light on the concept of recycling potential, end-of-life functional recycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 99 publications
0
12
0
Order By: Relevance
“…The results coincide with research by Dodman et al (2017) and OECD (2021), who identified cities as a sink of natural resources. Considering cities as potential resource stocks (Ghisellini et al, 2022), we can establish an effective mechanism to harness the resources and return them to the loop (Haberl et al, 2021), as identified by concepts of ‘recycling’, ‘reuse’, ‘recovery’, and ‘treatment’. Further evolution of only treating resources within circular cities is implementing urban manufacturing (Hausleitner et al, 2022), identified by concepts of ‘manufacture’ and ‘materials’.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results coincide with research by Dodman et al (2017) and OECD (2021), who identified cities as a sink of natural resources. Considering cities as potential resource stocks (Ghisellini et al, 2022), we can establish an effective mechanism to harness the resources and return them to the loop (Haberl et al, 2021), as identified by concepts of ‘recycling’, ‘reuse’, ‘recovery’, and ‘treatment’. Further evolution of only treating resources within circular cities is implementing urban manufacturing (Hausleitner et al, 2022), identified by concepts of ‘manufacture’ and ‘materials’.…”
Section: Discussionmentioning
confidence: 99%
“…By closer inspection, we identified four topics: urban mining, circular indicators, adaptive reuse , and regeneration . Urban mining relates to increasing the city's self‐reliance by utilising existing resources already stored within them (Ghisellini et al, 2022). The emerging topic suggests that cities are looking for additional ways to optimise their resource consumption, increase flow values and improve beneficial social and environmental improvements (Kakkos et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, construction industry stakeholders often overlook these waste streams, resulting in low recycling rates and environmental consequences. 17 In this sense, it is central to generate data related to flows and stocks of materials at national and regional level and in addition, to identify the possible economic benefits for each material. 18 Research into construction-focused urban mining has demonstrated considerable promise and advance.…”
Section: Cities Materials Stock and Urban Miningmentioning
confidence: 99%
“…WEEE prevention and valorization [6][7][8] in a Circular Economy perspective [9] are therefore necessary resource savings measures to preserve the known natural deposits of these scarce materials [10] and continue to rely on them for the manufacturing of new technological devices. The EU has defined lists of Strategic Raw Materials and Critical Raw Materials.…”
Section: Introductionmentioning
confidence: 99%